Battery-like behavior of Ni-ceria based systems: Synthesis, surface defects and electrochemical assessment. Issue 6 (15th April 2019) - Araújo, Allan J.M.; Silva, Vinícius D.; Sousa, Angel R.O.; Grilo, João P.F.; Simões, Thiago A.; Macedo, Daniel A.; Nascimento, Rubens M.; Paskocimas, Carlos A.
Abstract: NiO, CeO2 and respective composites are extensively used in energy storage devices due to mostly their high electrochemical activity. However, the assessment of battery-like behavior of Ni-ceria based systems comprising (Ni or Gd)-doped ceria combined with NiO seems to be neglected in the literature. In this work, NiO and ceria-based solid solutions composite powders were obtained by a co-precipitation synthesis method. The structure and particle size of the calcined powders were investigated by X-ray diffractometry (XRD) and field emission scanning electron microscopy (FESEM), respectively. Oxidative states of composites were inspected by X-ray photoelectron spectroscopy (XPS). The electrochemical performance of powders was evaluated by cyclic voltammetry, galvanostatic charge-discharge and impedance spectroscopy. Refinement of the XRD patterns showed that powders have nanosized crystallites and mean size of particles within 20 – 70 nm were revealed by FESEM. The improved specific capacity of the NiO-CeO2 electrode material (about 2.5 times higher than that of NiO-CGO at 5 mV s −1 ) is due to an increase in Faradic reactions taken place on its surface with a higher fraction of defects (namely Ni 3+, Ce 3+ and oxygen vacancies), as determined by XPS. The superior electrochemical performance of the NiO-CeO2 electrode is also confirmed by electrochemical impedance spectroscopy. Graphical abstract: fx1 Highlights: Ni-ceria based systems as battery-like materials; (Ni or Gd)-doping effect on the performance of ceria in alkaline (3 M KOH) solution; NiO + Ce-Ni-O solid solution with better battery-like behavior than NiO-Ce0.9 Gd0.1 O1.95 . Battery-like behavior enhanced by surface defects.